Soundscapes of Loyalty: Modeling Revisit Intention in Ethnic Music Tourism within a Sustainable Tourism Framework - Suhud, Usep; Sania, Nur; Prabawani, Bulan; Azinuddin, Muaz; Ibadullaev, Ergash; Sherov, Alisher; Bekchanov, Faxriddin; Matkarimov, Feruz (Journal of Posthumanism, 2025)
In spite of increasing popularity of music tourism, few studies have investigated consumer behaviour in ethnic music tourism. Filling this research lacuna, the present research examines determinants of tourists’ revisit intention to an ethnic music site—Saung Angklung Udjo, an iconic destination in Bandung, Indonesia. Drawing upon structural equation modelling with dataset of 250 respondents, this research investigates impacts of travel motivation, destination image, memorable tourism experience (MTE) and tourist satisfaction on revisit intention. The results of the analysis suggest that all hypothesised relationships are significant. Specifically, MTE has strong impacts on destination image, satisfaction and revisit intention, and travel motivation determines experience as well as post-visit outcomes. The findings highlight the pivotal role of immersion in culture in initiating consumer loyalty and enriching tourist experiences. This study contributes to music tourism by illustrating how ethnic performances do not only represent acts of culture as tourist attractions, but can serve as strategic resources of sustainable destination marketing. Saung Angklung Udjo provides an exemplar of how culture-based music tourism can sustain cultural heritage, local economies and intersubjective outcomes of interaction between tourists and locals. The results of the analyses provide both theoretical and practical implications to tourism managers to conceive culturally authentic, emotive, and sustainability-focused visitor experiences.